Non-adiabatic quantum dynamics of the ultracold Li+LiNa→ Li2+Na chemical reaction. Issue 12 (January 2020) - Kendrick, B K; Li, M; Li, H; Kotochigova, S; Croft, J F E; Balakrishnan, N
Synopsis: We report non-adiabatic dynamics of the Li+LiNa→Li2 +Na chemical reaction at cold and ultracold temperatures employing accurate ab initio electronic potential energy surfaces in a quantum dynamics formulation employing a diabatic representation. Results are compared against those from a single adiabatic ground state potential energy surface and a universal model based on the long-range interaction potential. We discuss signatures of non-universal behavior in the total rate coefficients as well as strong non-adiabatic effects in the state-to-state rotationally resolved rate coefficients.